The Effect of Vitamin D Deficiency on the Severity of Bronchiolitis in Infants - Meltem Erol; Hüseyin Kaya; Özlem Bostan Gayret; Özgül Yiğit; Şahin Hamilçıkan; Emrah Can (Galenos Yayinevi, 2017)
Aim: This study was conducted to investigate the effect of vitamin D deficiency on the severity of bronchiolitis in infants who were hospitalized for treatment. Materials and Methods: The infants who were followed up in our hospital and monitored due to acute bronchiolitis within a 0 to 24-month period were included in the study. The cases were evaluated by the clinical characteristics scoring system and divided into two groups (mild and moderate-severe). A questionnaire filled in by the mothers of the children to question the factors associated with vitamin D. The vitamin D levels of the cases, their clinical histories, and histories of taking vitamin D were examined. Results: The number of patients with a vitamin D level <20 ng/mL in the moderate-severe disease group was higher than the number in the mild disease severity group (p<0.05). No difference was detected in the number of patients who received vitamin D prophylaxis between the moderate-severe and mild disease severity groups (p>0.05). The number of patients with vitamin D level <20 ng/mL was higher in the hospitalized group than in the non-hospitalized group (p<0.05). There was no difference in the number of patients that received vitamin D prophylaxis between the hospitalized and the non-hospitalized groups (p>0.05). Conclusion: Vitamin D deficiency in infants is associated with increased severity of bronchiolitis and hospitalization.